Molecular cloning and characterization of the porcine prostaglandin transporter (SLCO2A1): evaluation of its role in F4 mediated neonatal diarrhoea - Van Poucke, Mario (BioMed Central, 2009)
BACKGROUND: Because prostaglandins are involved in many (patho)physiological processes, SLCO2A1 was already characterized in several species in an attempt to unravel specific processes/deficiencies. Here, we describe the molecular cloning and characterization of the porcine ortholog in order to evaluate its possible involvement in F4 enterotoxigenic E. coli mediated neonatal diarrhoea, based on a positional candidate gene approach study. RESULTS: Porcine SLCO2A1 is organized in 14 exons, containing an open reading frame of 1935 bp, encoding a 12-transmembrane organic anion cell surface transporter of 644 aa. The -388 to -5 upstream region comprises a (CpG)(48 )island containing a number of conserved promoter elements, including a TATA box. A potential alternative promoter region was found in the conserved -973 to -700 upstream region. No consensus polyadenylation signal was discovered in the 3' UTR. Repeat sequences were found in 15% of all the non coding sequences. As expected for a multifunctional protein, a wide tissue distribution was observed. mRNA expression was found in the adrenal gland, bladder, caecum, colon (centripetal coil/centrifugal coil), diaphragm, duodenum, gallbladder, heart, ileum, jejunum, kidney, liver, longissimus dorsi muscle, lung, lymph node, mesenterium, rectum, spleen, stomach, tongue and ureter, but not in the aorta, oesophagus and pancreas. The promoter region and the exons (including the splice sites) of SLCO2A1 were resequenced in 5 F4ab/ac receptor positive and 5 F4ab/ac receptor negative pigs. Two silent and 2 missense (both S → L at position 360 and 633) mutations were found, but none was associated with the F4ab/ac receptor phenotype. In addition, no phenotype associated differential mRNA expression or alternative/abberant splicing/polyadenylation was found in the jejunum. CONCLUSION: The molecular cloning and characterization of porcine SLCO2A1 not only contributes to the already existing knowledge about the transporter in general, but enables studies on porcine prostaglandin related processes/deficiencies as patient and/or model. Here we examined its possible involvement as receptor in F4 enterotoxigenic E. coli mediated neonatal diarrhoea. Because no phenotype associated differences could be found in the gene sequence nor in its jejunal transcription profile of F4ab/ac receptor positive/negative pigs, SLCO2A1 can most likely be excluded as receptor for F4 bacteria.